2008
DOI: 10.5194/angeo-26-1741-2008
|View full text |Cite
|
Sign up to set email alerts
|

The formation of sporadic E layers by a vortical perturbation excited in a horizontal wind shear flow

Abstract: Abstract. The formation of the mid-latitude sporadic E layers (E s layers) by an atmospheric vortical perturbation excited in a horizontal shear flow (horizontal wind with a horizontal linear shear) is investigated. A three-dimensional atmospheric vortical perturbation (atmospheric shear waves), whose velocity vector is in the horizontal plane and has a vertical wavenumber k z =0, can provide a vertical shear of the horizontal wind. The shear waves influence the vertical transport of heavy metallic ions and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This is caused by the influence of cyclone-type background flow on the ions convergence process. In the presented work we further extend the study by Didebulidze and Lomidze (2008;. In those works it was shown that stationary atmospheric vortical perturbation (shear wave with a zero frequency), evolving in the horizontal shear flow, can be responsible for the horizontal and vertical convergence of ions and for the formation of multilayered sporadic-E.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This is caused by the influence of cyclone-type background flow on the ions convergence process. In the presented work we further extend the study by Didebulidze and Lomidze (2008;. In those works it was shown that stationary atmospheric vortical perturbation (shear wave with a zero frequency), evolving in the horizontal shear flow, can be responsible for the horizontal and vertical convergence of ions and for the formation of multilayered sporadic-E.…”
Section: Discussionmentioning
confidence: 83%
“…, the function associated with AGWs is employed (Didebulidze and Lomidze, 2008;Didebulidze and Pataraya, 1999):…”
Section: Horizontal and Vertical Drift Of Ions Under The Influence Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The shear wave velocity can change its polarization in regions with thickness of about half of its vertical wavelength λ z /2, and it can result in the increase of the upstream and downstream flows of ions along the midlatitude declined magnetic field via combined action of ion‐neutral collisional coupling and Lorentz forcing [ Didebulidze and Lomidze , 2008]. In Figure 2 for heights about λ z /2 above F 2 layer peak the northward wind decreases (or the southward one increases), and for the considered parameters of shear wave the F 2 layer peak is formed above its main peak.…”
Section: Theoretical Resultsmentioning
confidence: 99%